European Respiratory Society guidelines on long-term home non-invasive ventilation for management of COPD. Issue 3 (28th September 2019) - Ergan, Begum; Oczkowski, Simon; Rochwerg, Bram; Carlucci, Annalisa; Chatwin, Michelle; Clini, Enrico; Elliott, Mark; Gonzalez-Bermejo, Jesus; Hart, Nicholas; Lujan, Manel; Nasilowski, Jacek; Nava, Stefano; et al.
Background: While the role of acute non-invasive ventilation (NIV) has been shown to improve outcome in acute life-threatening hypercapnic respiratory failure in COPD, the evidence of clinical efficacy of long-term home NIV (LTH-NIV) for management of COPD is less. This document provides evidence-based recommendations for the clinical application of LTH-NIV in chronic hypercapnic COPD patients. Materials and methods: The European Respiratory Society task force committee was composed of clinicians, methodologists and experts in the field of LTH-NIV. The committee developed recommendations based on the GRADE (Grading, Recommendation, Assessment, Development and Evaluation) methodology. The GRADE Evidence to Decision framework was used to formulate recommendations. A number of topics were addressed under a narrative format which provides a useful context for clinicians and patients. Results: The task force committee delivered conditional recommendations for four actionable PICO (target population-intervention-comparator-outcome) questions, 1) suggesting for the use of LTH-NIV in stable hypercapnic COPD; 2) suggesting for the use of LTH-NIV in COPD patients following a COPD exacerbation requiring acute NIV 3) suggesting for the use of NIV settings targeting a reduction in carbon dioxide and 4) suggesting for using fixed pressure support as first choice ventilator mode. Conclusions: Managing hypercapnia may be an important intervention for improving the health outcome of COPD patients with chronic respiratory failure. The task force conditionally supports the application of LTH-NIV to improve health outcome by targeting a reduction in carbon dioxide in COPD patients with persistent hypercapnic respiratory failure. These recommendations should be applied in clinical practice by practitioners that routinely care for chronic hypercapnic COPD patients. Managing hypercapnia may be an important intervention for improving outcome of COPD patients with chronic respiratory failure. Long-term home NIV may improve health outcomes by targeting a reduction in CO2 in those with hypercapnic respiratory failure. http://bit.ly/2NlA3eG